2013
DOI: 10.1038/bjc.2013.264
|View full text |Cite
|
Sign up to set email alerts
|

Expression of neutrophil gelatinase-associated lipocalin in colorectal neoplastic progression: a marker of malignant potential?

Abstract: Background:Neutrophil gelatinase-associated lipocalin (NGAL) has a diverse functional repertoire, involved in the innate immune response as well as cell growth and differentiation. Expression has been linked to malignant disease development and progression.Methods:Neutrophil gelatinase-associated lipocalin expression was assessed immunohistochemically in 98 colorectal neoplastic lesions (52 cancer polyps (CaPs) and 46 sporadic adenoma/adjacent normal mucosa paired specimens) to investigate association with ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 24 publications
0
15
1
Order By: Relevance
“…In our study, the increase in serum NGAL concentration in patients with CRC was moderate since NGAL concentration was on average 28% higher in CRC patients than in controls, varying between 11% in stage 0-I and 66% in stage IV. Our results along with those reported by other studies both in the oncology field and in other fields [ 14 , 21 , 25 , 39 41 ] contrast with the recent observation of 145- and 185-fold increases in serum NGAL in non-metastatic and metastatic CRC respectively, compared to controls [ 30 ]. Besides differences in study design, the lower increase in serum NGAL in our study could be partly explained by differences in NGAL measurement techniques.…”
Section: Discussioncontrasting
confidence: 57%
“…In our study, the increase in serum NGAL concentration in patients with CRC was moderate since NGAL concentration was on average 28% higher in CRC patients than in controls, varying between 11% in stage 0-I and 66% in stage IV. Our results along with those reported by other studies both in the oncology field and in other fields [ 14 , 21 , 25 , 39 41 ] contrast with the recent observation of 145- and 185-fold increases in serum NGAL in non-metastatic and metastatic CRC respectively, compared to controls [ 30 ]. Besides differences in study design, the lower increase in serum NGAL in our study could be partly explained by differences in NGAL measurement techniques.…”
Section: Discussioncontrasting
confidence: 57%
“…Currently, the roles of LCN2 in human neoplasia attract attention because its increased expression has been observed in malignant tumors and its pro‐tumoral effects have been observed in epithelial ovarian cancer, pancreatic cancer, and esophageal cancer . In colon cancer, it has also observed that LCN2 overexpressed during the transition from adenoma to carcinoma, indicating that LCN2 drives tumor progression . Meanwhile, the antitumoral and antimetastatic effects of LCN2 were demonstrated in hepatocellular carcinoma, lung cancer, and pancreatic cancer .…”
Section: Discussionmentioning
confidence: 99%
“…47 In colon cancer, it has also observed that LCN2 overexpressed during the transition from adenoma to carcinoma, indicating that LCN2 drives tumor progression. 51,52 Meanwhile, the antitumoral and antimetastatic effects of LCN2 were demonstrated in hepatocellular carcinoma, 53 lung cancer, 54 and pancreatic cancer. 55 The cell type-specific function of LCN2 remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels in colon cancer cases then controls were observed by Fung KY et al but the authors concluded that it was not a promising biomarker for the diagnosis of CRC as the sensitivity of NGAL was found to be 24% at 90% specificity [46]. Accordingly, although NGAL is still expressed by the majority of human neoplastic colorectal lesions, the author it is not a useful biomarker for determining disease progression from adenomatous to malignant colorectal neoplasia [47]. Our analysis, in line with the majority of previous studies, shows the upregulation of NGAL in adenocarcinoma tumor samples and reduced expression in metastatic samples.…”
Section: Discussionmentioning
confidence: 99%